1995
DOI: 10.1210/jcem.80.8.7543113
|View full text |Cite
|
Sign up to set email alerts
|

Potential of testosterone buciclate for male contraception: endocrine differences between responders and nonresponders.

Abstract: Suppression of serum LH and FSH, by testosterone (T) alone or in combination with other agents, has proved to be the most promising approach to male contraception. T enanthate, the only androgen preparation tested in male contraceptive efficacy trials so far, must be injected every week due to its short terminal elimination half-life of 4.5 days and leads to supraphysiological T serum levels. A new T ester synthesized under WHO and NIH auspices, testosterone buciclate (TB), showed a favorable pharmacokinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
3
33
1
Order By: Relevance
“…The longacting testosterone ester testosterone buciclate was identified under the auspices of WHO and NIH and showed a half-life of 29.5 days when tested in hypogonadal men, much longer than the 4.5 days of testosterone enanthate 9 . Suppression of spermatogenesis was comparable to that of weekly testosterone enanthate injections, reaching azoospermia in three out of eight volunteers after a single injection of 1200 mg of testosterone buciclate.…”
Section: T E S T O S T E R O N E a L O N Ementioning
confidence: 99%
“…The longacting testosterone ester testosterone buciclate was identified under the auspices of WHO and NIH and showed a half-life of 29.5 days when tested in hypogonadal men, much longer than the 4.5 days of testosterone enanthate 9 . Suppression of spermatogenesis was comparable to that of weekly testosterone enanthate injections, reaching azoospermia in three out of eight volunteers after a single injection of 1200 mg of testosterone buciclate.…”
Section: T E S T O S T E R O N E a L O N Ementioning
confidence: 99%
“…Further clinical studies showed a maximum concentration 9 weeks postinjection of 13.1 T 1.8 nmol/L, the half-life being about 30 days. An injection of 1000 mg testosterone buciclate maintained testosterone serum levels within the normal range up to week 16 (95).…”
Section: Parenteral Deliverymentioning
confidence: 85%
“…The control of fertility is a major public health issue [1,2]. FSH receptor (FSHR) antagonists could potentially represent a novel nonsteroidal approach for contraception due to their specific action on ovarian tissue without affecting peripheral and central tissues.…”
Section: Introductionmentioning
confidence: 99%